Role of sport medicine professionals in addressing psychosocial aspects of sport-injury rehabilitation: professional athletes' views - Arvinen-Barrow, M.; Massey, W. V.; Hemmings, B. (Journal of Athletic Training, 2015)
Context: Research from the sport medicine professional's (SMP's) perspective indicates that SMPs are often required to address psychosocial aspects of injuries during treatment. However, only a few authors have investigated injured athletes' experiences with these concerns.